Responsabilidad internacional pública de las empresas transnacionales por la violación de los derechos humanos (2020)
There are frequent cases of human rights violations, in which the protagonists are transnational companies, through their subsidiaries present in states with weak legal systems, mainly in Latin American, Asian and African countries, which do not have effective grievance mechanisms to guarantee the human rights of victims. Cases such as the death of union leaders of the subsidiaries of Coca-Cola Company Co., in Colombia, at the hands of paramilitary groups, allegedly sponsored by executives of that Company, and in which the victims have not obtained the reparation of their damages, increases the levels of impunity in the field of human rights. The foregoing, demonstrates the need for a binding human rights instrument to be enacted in the orbit of public international law, which allows for the determination of the international responsibility of transnational Corporations and the reparation of victims' damages, since the instruments currently, such as the Guiding Principles on Business and Human Rights, of the United Nations Human Rights Council, are soft law provisions, which, although it is true, have promoted Corporate Social Responsibility, they are not binding instruments for Corporations Transnationals